1983
DOI: 10.1007/bf01252809
|View full text |Cite
|
Sign up to set email alerts
|

Functional synaptogenesis and the rat pineal gland: A pharmacological investigation

Abstract: Pineal glands obtained from rats of different ages were incubated in vitro with drugs known to specifically alter pre- or postsynaptic noradrenergic neurotransmission to determine when during development nerve terminal or receptor mediated control of glandular N-acetyltransferase (NAT) activity might reach functional maturation. Basal daytime NAT activity measured in vitro was lowest in fetal rats, increased dramatically by the day of birth, peaked at 10 days postnatally, and subsequently declined to near adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1987
1987
1992
1992

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Since neonatal rats are ectothermic for the first few weeks of life (Hill, 1947;Lytle and Keil, 1974), and neonatal hypothermia causes elevations in pineal gland NAT activity (Torres et al, 1989), all animals were kept at 35 ~ (nest temperature) on a medical heating pad which subsequently maintained their body temperatures at approximately 34-35 ~ Rectal temperatures were measured at the end of the 4 hr period of dark or light exposure by means of a lubricated thermocouple (Model BAT-12) inserted ~ 1 cm beyond the anal sphincter. Shortly thereafter intact or enucleated pups were decapitated and pineal glands were rapidly excised and frozen at -70 ~ until assayed for NAT activity using a modification (Altar et al, 1983) of the method of Deguchi and Axelrod (1972). Data were analyzed by analysis of variance tests followed by post hoc comparisons using Student's t-tests.…”
Section: Methodsmentioning
confidence: 99%
“…Since neonatal rats are ectothermic for the first few weeks of life (Hill, 1947;Lytle and Keil, 1974), and neonatal hypothermia causes elevations in pineal gland NAT activity (Torres et al, 1989), all animals were kept at 35 ~ (nest temperature) on a medical heating pad which subsequently maintained their body temperatures at approximately 34-35 ~ Rectal temperatures were measured at the end of the 4 hr period of dark or light exposure by means of a lubricated thermocouple (Model BAT-12) inserted ~ 1 cm beyond the anal sphincter. Shortly thereafter intact or enucleated pups were decapitated and pineal glands were rapidly excised and frozen at -70 ~ until assayed for NAT activity using a modification (Altar et al, 1983) of the method of Deguchi and Axelrod (1972). Data were analyzed by analysis of variance tests followed by post hoc comparisons using Student's t-tests.…”
Section: Methodsmentioning
confidence: 99%
“…The peak that occurred in nighttime levels of NAS in 10-day-old pups may simply reflect day-to-day variability in the phase of the rhythm. However, a dramatic rise in pineal NAT activity and plasma melatonin has been reported to occur at 10 days of age [Altar et al, 1983;Murakami et al, 19891. The age-related decline in tryptophan is associated with the rise in 5HT, although substrate utilization is probably not the only mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple pair-wise comparisons indicated that this effect of age on NAS was the result of elevated nighttime levels in 10-day-old animals ( Fig. 12b) reflecting the dramatic increase in the pineal N-acetyltransferase enzyme which has been reported to occur at 10 days of age (Altar et al, 1983).…”
Section: Relationship Of Sr To Melatonin Productionmentioning
confidence: 95%